Does interfacial exciton quenching exist in high-performance quantum dot light-emitting diodes?. Issue 7 (26th January 2023) - Qu, Xiangwei; Liu, Wenbo; Li, Depeng; Ma, Jingrui; Gu, Mi; Jia, Siqi; Xiang, Guohong; Sun, Xiao Wei
Abstract : Exciton quenching at the QD–ETL interface is unintentionally avoided, which bridges interfacial exciton quenching and high performance in a quantum dot light-emitting diode. Abstract : In quantum dot light-emitting diodes (QLEDs), even seemingly with interfacial exciton quenching between quantum dots (QDs) and the electron transport layer (ETL) limiting the device efficiency, the internal quantum efficiency of such QLEDs approaches 100%. Therefore, it is a puzzle that QLEDs exhibit high performance although they suffer from interfacial exciton quenching. In this work, we solve this puzzle by identifying the cause of the interfacial exciton quenching. By analyzing the optical characteristics of pristine and encapsulated QD–ETL films, the interfacial exciton quenching in the pristine QD–ETL film is attributed to O2 -induced charge transfer. We further investigate the charge transfer mechanism and its effect on the performance of QLEDs. Finally, we show the photodegradation of the pristine QD–ETL film under UV irradiation. Our work bridges interfacial exciton quenching and high performance in hybrid QLEDs and highlights the significance of encapsulation in QLEDs.